Effects of plant-based fermented broth on rumen fermentation, gastrointestinal development, and microbial populations in fattening lambs - Zhang, Lu; Zhang, Huiwen; Song, Lianjie; Li, Yongliang; Guo, Jianjun; Li, Feng; Li, Bosen; Chen, Wei; Liu, Yuqing; Yang, Haitong; Li, Jianjie; Gao, Yuhong; et al. (Frontiers in Veterinary Science, 2025)
IntroductionDigestive dysfunction in lamb fattening has been a concern in recent years. The objective of this study was to investigate the effects of a fermentation broth (FB) derived from eight plants on rumen fermentation, gastrointestinal development, and microbial community composition in fattening lambs through in vitro and in vivo experiments.MethodsIn vitro rumen fermentation was performed with six FB: diet ratios (mL/g): 0, 1:125, 1:250, 1:500, 1:1000, and 1:2000. Fermentation parameters and nutrient disappearance rates were measured over 48 h. Based on the results of the in vitro test, two optimal doses of FB (1:500 and 1:1000) were selected for further in vivo testing over a 120-day period. A total of 90 weaned small-tailed Han lambs were assigned to three groups, receiving FB in drinking water at 0 (control), 1:500, or 1:1000 (vol/vol).ResultsThe results showed that three parameters of gas production (GP), including fast-degradable fraction, slow-degradable fraction, and theoretical GP, were significantly higher (p < 0.05) in the 1:500 and 1:1000 groups compared with other groups. In vivo tests further showed that FB supplementation at 1:500 and 1:1000 improved rumen microstructure (papilla length, papilla surface, mucosa thickness, and muscle thickness) and jejunal microstructure (villus height, villus surface, and muscle thickness). Moreover, two rumen bacterial indices, PD_whole_tree (p = 0.06) and Shannon (p = 0.07), demonstrated increasing trends in both FB groups relative to the control group. In the rumen, 1:500 FB supplementation increased the abundance of Firmicutes (p < 0.01) and decreased Bacteroidota abundance (p < 0.01). In the jejunum, 1:500 FB supplementation decreased the abundance of Euryarchaeota and Methanobrevibacter (both p = 0.02) while increasing the abundance of Actinomycetes and Aeriscardovia (both p = 0.01) compared to the control.DiscussionIn summary, FB supplementation in lambs’ drinking water at a ratio of 1:500 (FB: diet, mL/g) improved rumen fermentation and promoted microecological balance.